Toll‑like receptors ligand immunomodulators for the treatment congenital diaphragmatic hernia. - Vallejo-Cremades, Mayte; Merino, Javier; Carmona-Mejías, Rita María; Córdoba, Laura; Salvador, Beatriz; Martínez, Leopoldo; Tovar, Juan Antonio; Llamas, Miguel Ángel; Muñoz-Chápuli-Oriol, Ramón; Fresno, Manuel (BMC, 2024)
Congenital diaphragmatic hernia (CDH) is a rare disease that affects the development of the diaphragm, leading to abnormal lung development. Unfortunately, there is no established therapy for CDH. Retinoic acid pathways are implicated in the ethology of CDH and macrophages are known to play a role in repairing organ damage. We have analyzed the effect of several Toll like receptor (TLR) ligands in the nitrofen-induced CDH model in pregnant rats widely used to study this disease and in the G2-GATA4Cre;Wt1fl/fl CDH genetic mice model. Morphometric and histological studies were carried out. Immune cell infiltration was assayed by immunochemistry and immunofluorescence and retinoic pathway gene expression analyzed in vivo and in vitro in macrophages. Our research has shown that TLR ligand immunomodulators that influence anti-inflammatory macrophage activation can be effective in treating CDH, being nontoxic for the mothers or pups suggesting that those TLR ligands are a promising solution for CDH leading to orphan drug designation for CS1. The immune system of the fetus would be responsible for repairing the damage and closure of the hernia in the diaphragm and enhanced proper lung development after CS1 treatment.
Keywords: Cardiopatía congénita; Corazón - Embriología; Genética del desarrollo; Macrófagos; Interacción celular; Fetal therapy; Toll-like receptors; Macrophages; Inflammation; Retinoic pathway; Embryonic development; Congenital diaphragmatic hernia; Orphan drug